Nitrogen fertilization of Cabernet Sauvignon grapevines: yield, total nitrogen content in the leaves and must composition - Felipe Lorensini; Carlos Alberto Ceretta; Cledimar Rogério Lourenzi; Lessandro De Conti; Tadeu Luis Tiecher; Gustavo Trentin; Gustavo Brunetto (Acta Scientiarum: Agronomy, 2015)
Grapevines grown on sandy soils are subjected to the application of supplemental nitrogen (N); however, there is little information available regarding the impact of these applications on yield, plant nutritional state and must composition. The aim of this study was to evaluate the yield, nutritional state and must composition of grapevines subjected to N fertilization. Cabernet Sauvignon grapevines were subjected to annual applications of 0, 10, 15, 20, 40, 80 and 120 kg N ha-1 in 2008, 2009 and 2010. During the 2008/09, 2009/10 and 2010/11 harvest seasons, leaves were collected during full flowering and when the berries changed color, and the total N content was analyzed. The grape yield and the enological characteristics of the must were evaluated. The response to applied N was low, and the highest Cabernet Sauvignon grape yield was obtained in response to an application of 20 kg N ha-1 year-1. The application of N increased the nutrient content in the leaf collected at full flowering, but it had little effect on the total nutrient content in the must, and it did not affect the enological characteristics of the must, such as soluble solids, pH, total acidity, malic acid and tartaric acid.